Mathematical Modelling of Robust Optimization for Integer Programming Problem - Thapa, Gyan Bahadur (Journal of Institute of Science and Technology, 2015)
Dealing with data uncertainty in mathematical programming has been recognized as a central problem in optimization for a long time. There are two methods that have been proposed to address data uncertainty over the years, namely stochastic programming and robust optimization. In this short paper, we present the brief review of mathematical models of integer programming problem and robust optimization approach to solve them. Robust Binary optimization is also briefly presented. Journal of Institute of Science and Technology, 2015, 20(1): 119-122